The Influence of Locus Of Control on Self-Awareness in Narcotics LAPAS - Maulida, Dara; Siregar, Mawardi; Chalidaziah, Wan (Universitas Negeri Medan, 2024)
A person's self-awareness affects the decisions that will be made, whether in making a decision to solve a problem or making decisions for his survival. Locus of Control becomes one of the most determining factors of an individual's behavior. An individual who commits a social deviation, then they will be responsible for what has been done, in this case the authors use the prisoners of Class II Narcotics Layer Slow as the object of research. The study aims to find out the picture of the locus of control and Self-awareness in the prisoner as well as the influence of the local of control on self-consciousness in the NAPAS Drug Class II Slow. The sampling techniques used in this study were random samplings, a population of 470 prisoners researchers and samples determined 217 samples. The results of the study obtained an overview of the locus of control prisoners as a whole were in the middle category, the overall self-awareness of the prisoner was in the high category, and the results of a simple double linear regression test in obtaining the results from the t table 0.042<0.05 had no significant influence on the locuse of control on self- awareness in the prisoner.